2007
DOI: 10.1007/s10725-007-9168-0
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous GA3 overcomes bud deterioration in tulip (Tulipa gesneriana L.) bulbs during dry storage by promoting endogenous IAA activity in the internodes

Abstract: Endogenous free IAA was examined with an immunohistochemical method for its involvement in the reduction of bud deterioration after GA 3 was injected into the bulbs. We found that tulip bulbs stored at 20°C constantly developed severe bud deterioration, whereas the symptoms of deterioration was lighter in the bulbs with GA 3 injection and not observed in the bulbs with 4°C treatment. 73% success in overcoming bud deterioration was achieved in 20°C with GA 3 treatment after 8 weeks of bulb storage, and the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Thus, the ratio of two hormones is equally important as the level of a single hormone. In pea (Pisum sativum; Law and Hamilton, 1984) and tulip (Tulipa gesneriana; Xu et al, 2007), GA 3 application (0.45 mM by spray and 0.8 mg • mL -1 by injection, respectively) increased the content of indoleacetic acid (IAA). In addition, IAA can promote the biosynthesis of GA 1 in pea (P. sativum; Ross et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ratio of two hormones is equally important as the level of a single hormone. In pea (Pisum sativum; Law and Hamilton, 1984) and tulip (Tulipa gesneriana; Xu et al, 2007), GA 3 application (0.45 mM by spray and 0.8 mg • mL -1 by injection, respectively) increased the content of indoleacetic acid (IAA). In addition, IAA can promote the biosynthesis of GA 1 in pea (P. sativum; Ross et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of fruit flesh firmness was duo to the increase of original pectin, lignin and cellulose contents with the storage [21] . Exogenous GA 3 was reported to increase the content of endogenous GA 3 , resulting in a lower ratio of ABA/GA 3 value, while restrain the activity of PAL and POD, resulting in a lower level of lignin and flesh firmness [16] . The fruit flesh firmness of the control group increased by 31.33% at 14-d storage when compared to the beginning value.…”
Section: Bchanges Of Flesh Firmness During Storagementioning
confidence: 99%
“…Gibberellin (GA3) was a kind of phytohormone. It was shown that GA3 would benefit the storage quality of tulip bulb [16] , bamboo shoot [17] , jujube [18] and Broccoli curd [19] , etc. The effect of GA3 on the storage quality of post-harvest loquat was still not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these localization methods, the distinct advantage of the immunohistochemical (IHC) method is its specific recognition of target analytes by monoclonal antibodies (mAbs). The technique has been used in studies of macromolecules, such as cytochromes [ 21 ], pectins [ 22 ], oxidized proteins [ 23 ], sulfurtransferase [ 24 ],glycine-rich proteins [ 25 ] and small bioactive molecules, such as indole-3-acetic acid [ 26 , 27 ], gibberellic acid 3 [ 28 ] and abscisic acid [ 29 ]. The accurate localization plays a great role in illustrating the physiological function of these compounds in the plant.…”
Section: Introductionmentioning
confidence: 99%